Kajian Geomorfologi Kawasan Wisata Batu Lubang - Ahmad Fahrizal; Ilham Marasabessy; Ilham Ilham; Neneng S. Kalidi; Neil A. Fonataba (Jurnal Airaha, 2022)
Batu Lubang Village has now become a tourist village, several coastal areas in this village have characteristics that can be an attraction for tourists with all the characteristics, beauty and authenticity of the environment, namely underwater life in the waters, the shape of the beach with beach sand, waterfalls. , caves, etc.), coastal forests which have a rich variety of plants, birds and other animals. This study aims to identify the geomorphological conditions of the Batu Hole Pantai tourist area as a first step to determine the characteristics of the Batu Hole Pantai tourist area, Makbon District, Sorong Regency. This research was conducted in the village of Batu Hole Beach in August-September. Geomorphological parameters discussed include beach type, beach width and length, land cover, beach slope, and water depth. Analysis of the data used is based on Geographic Information Systems (GIS). The results of the data were analyzed descriptively qualitatively. The results showed that the characteristics of Batu Hole tourism have beach types from sandy to rocky, beach width of more than 15 meters, flat beach slope, land cover in the form of open land, mangroves, and near coconut trees, depth of coastal waters including shallow category, and basic substrate. The waters vary from sandy, loam to sandy and rocky.